Adjacency Pairs in Puss in Boots: The Last Wish - Ni Kadek Suarti; Made Susini; Radha Andhra Swari (British (Jurnal Bahasa dan Sastra Inggris), 2026)
Adjacency pairs play a crucial role in organizing speech, guiding responses, and ensuring a smooth flow of communication in conversation. Misunderstandings and disruptions in adjacency pairs, such as unexpected responses or preference violations, often occur, affecting the coherence and effectiveness of interactions. The adjacency pair patterns applied in conversation are heavily dependent on the context of conversation, such as popular media, classroom studies, and others. Deploying Schegloff’s conversation analysis, this study investigates adjacency pairs in the animated film Puss in Boots: The Last Wish. The data are in the form of dialogues and were collected from transcribed dialogues found in the film. The results of the analysis reveal that six types of adjacency pairs are found: greeting-greeting, offer-acceptance/rejection, request-compliance/refusal, invitation-acceptance/declination, question-answer, and assessment-agreement/disagreement. Due to the type of response the characters have, the characters act as two types of responses, and those are preferred and dispreferred responses. This result implies that the characters of animated film act naturally. This study provides insights into how adjacency pairs function within fictional discourse and enhances the understanding of conversational structures in animated films.